Aligning Intellectual Property Rights with Climate Imperatives: A Comparative Study of Plant Variety Protection - Lu Sudirman; Rufinus Hotmaulana Hutauruk; Agustianto Agustianto; Nurlaily Nurlaily; Hari Sutra Disemadi (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
Indonesia's agricultural sector has been ridden with stagnation and mismanagement, contrasting Singapore, which despite the lack of potential, has been able to facilitate its agricultural sector to thrive while aligning with sustainability. In this context, Indonesia's Plant Variety Protection (PVP) Law represents an IPR regime that can be analyzed further to explore the potential of helping Indonesia tackle climate change. This research analyzes the legal capacity of Indonesia’s PVP regime to integrate climate action initiatives, which provides a novel perspective by bridging intellectual property rights and sustainability, with the added comparative angle of Singaporean perspective. The findings of this research indicate that Indonesia's PVP regime is outdated and ill-equipped to accommodate the regime’s inherent potential in being a part of the climate action. In contrast, Singapore boasts a more robust legal framework that has facilitated the growth of its modern agricultural sector, despite resource constraints, along with the lack of direct normative connection between sustainability and the PVP regime, due to supporting normative architectures. The perspective from Singapore represents a potential model for Indonesia to consider as it seeks to enhance its PVP regime and align it with broader climate change mitigation strategies.